Identification of a Gene Sharing a Promoter and Peroxisome Proliferator-Response Elements With Acyl-CoA Oxidase Gene - Mst. Hasina Akter; Md. Abdur Razzaque; Liu Yang; Toshio Fumoto; Kiyoto Motojima; Tomohiro Yamaguchi; Fumiko Hirose; Takashi Osumi (PPAR Research)
Many mammalian genes are clustered on the genomes, and hence the genes in the same cluster can be regulated through a common regulatory element. We indeed showed previously that the perilipin/PEX11α gene pair is transactivated tissue-selectively by PPARγ and PPARα, respectively, through a common binding site. In the present study, we identified a gene, named GSPA, neighboring a canonical PPAR target, acyl-CoA oxidase (AOX) gene. GSPA expression was induced by a peroxisome proliferator, Wy14,643, in the liver of wild-type mice, but not PPARα-null mice. GSPA and AOX share the promoter and two peroxisome proliferator-response elements. GSPA mRNA was also found in the heart and skeletal muscle, as well as 3T3-L1 cells. GSPA encodes a protein of 161 amino acids that is enriched in 3T3-L1 cells. Even other gene pairs might be regulated through common sequence elements, and conversely it would be interesting how each gene is aptly regulated in clusters.